Geometry, Space, Configuration: a Meeting with Anna Sgrosso (diségno, 2019)
During the last Congress of the Unione Italiana per il Disegno,held in Naples, the 2017 UID Gold Medal was awardedto Anna Sgrosso with the aim of rewarding the complex ofscientific and cultural activities promoted at the Universityof Naples Federico II over a long and prestigious career.Thanks to her studies, both in architectural and mathematicalfields, Anna Sgrosso has revitalized Descriptive Geometry,finding new expressive and communicative impulsein the study of its projective roots and in the links that thisdiscipline establishes with the world of figuration and art.In particular, Anna Sgrosso’s proposal to use traditional representationsystems (Monge, axonometry, perspective) in an unconventional manner led to an innovative interpretationof architecture –realized or in progress–, in which itis possible to identify structure and geometric genesis ofthe spaces.